ALKOHOLISIS MINYAK JELANTAH MENJADI BIODIESEL DENGAN KATALIS ZEOLIT-ZIRKONIA TERSULFATASI - , PARAMITA DWI SUKMAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Used cooking oil is very potential to be developed as an alternative energy source for substitution of fosil fuel. Utilization of used cooking oil as raw material for biodiesel is one way of reducing waste (used cooking oil) that produce economic value and creating an alternative fuel for diesel fuel substitute. Used cooking oil can be processed into biodiesel by transesterification with methanol using zeolite sulfated zirconia catalyst. Transesterification of used cooking oil with sulfated zirconia zeolit catalyst was conducted in a batch reactor equipped with a heater, thermometer, stirrer, and tap of the sample taker. The reactor was filled with used cooking oil, methanol and catalyst and subsequent reaction ran for 120 minutes after the reaction temperature was reached and samples were taken every certain time interval. Esters were analyzed by iodometric titration. Variables which were studied in this research include the ratio of methanol to oil, reaction temperature, and concentration of catalyst. The higher the concentration of catalyst, methanol to oil ratio of reactants, and reaction temperature, the higher the conversion was obtained. The value of the collision frequency factor and activation energy for each step is 72,6751 1/minute and 7.581,649 kal/mol respectively. Relatively good condition to be achieved at the ratio of oil to methanol 1:6, 2% catalyst concentration, reaction temperature of 120oC, and reaction time for 120 minutes with a conversion of 71.62%. Key words : Used cooking oil, transesterification, zeolit sulfated zirconia, biodiesel